1997
DOI: 10.1017/s0043174500088925
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cross-resistance patterns in acetyl-CoA carboxylase inhibitor resistant wild oat (Avena fatua)

Abstract: The purpose of this study was to determine cross-resistance patterns among wild oat lines resistant to acetyl-CoA carboxylase (ACCase) inhibitors and to determine which, if any, cross-resistant type was more common than another. Discriminatory concentrations of two aryloxyphenoxy-propionates (APP) and three cyclohexanediones (CHD) were determined using a petri-dish bioassay. These concentrations were then applied to 82 resistant wild oat lines identified in previous studies. In addition, two resistant standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…Cross-resistance patterns were characterized using 82 ACCase inhibitor-resistant wild oat lines, in which lines were categorized into three resistant types, A, B, or C, based on cluster analysis (Bourgeois et al 1997). Type A was highly resistant to APP herbicides and had no or low resistance to CHD herbicides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-resistance patterns were characterized using 82 ACCase inhibitor-resistant wild oat lines, in which lines were categorized into three resistant types, A, B, or C, based on cluster analysis (Bourgeois et al 1997). Type A was highly resistant to APP herbicides and had no or low resistance to CHD herbicides.…”
Section: Resultsmentioning
confidence: 99%
“…Types B and C were low to moderately resistant (type B) and highly (type C) resistant to both APP and CHD herbicides, respectively. In their (Bourgeois et al 1997) study, type C was the most common cross-resistance Table 3. Herbicides and rates used in dose-response studies with five resistant (R1 to R5) and susceptible (S) wild oat biotypes.…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods have rarely been used outside research owing to the high costs involved, restrictions to target‐site resistance only and ambiguity arising from multiple amino acid changes at specific resistance codon positions . Equally, methods based on pollen, seeds, enzyme and metabolism assays have not been widely adopted because they do not cover all possible resistance mechanisms and are therefore prone to false negative prediction of resistance. To date, the classical whole‐plant test using seeds collected at the end of the growing season remains the most commonly employed method for confirming resistance to ACCase herbicides .…”
Section: Methods For Detecting Resistance To Accase Herbicidesmentioning
confidence: 99%
“…A. fatua is highly prone to evolving resistance, and indeed single‐resistant and multiple‐resistant populations have been found across western Canada. A. fatua has been reported to be resistant to group A, group B, group K 2 and N. However, after 15–20 years, resistance to triallate (N) in A. fatua has not expanded much and appears to remain at low levels (<10%) in Canada, probably because the pre‐emergence herbicide is not commonly used now. Glasshouse studies have shown that A. fatua populations are up to tenfold more resistant than susceptible lines .…”
Section: Three Major Cases Of Herbicide‐resistant Weeds In Three Cropmentioning
confidence: 99%